Developing Stroke Flexibility - Giffenig, Edgar (ITF Coaching & Sport Science Review, 2014)
Variability is the key to greatness in cooking, tennis and probably anything in life. True mastery can only be achieved through maturity, and maturity is nothing more than an accumulation of a great variety of experiences. Therefore, to develop more effective shots, the traditional way of training needs to be adjusted to allow players to practice with a much greater degree of variability, forcing the players to constantly adapt and thus develop the desired stroke flexibility.